1979
DOI: 10.1530/jrf.0.0550027
|View full text |Cite
|
Sign up to set email alerts
|

Total follicular populations in ewes of high and low ovulation rates

Abstract: The total ovarian follicular populations were studied in two breeds of ewes which differed greatly in their ovulation rates. Thus 8 Romanov (mean ovulation rate 3.1) and 12 Ile-de-France ewes (mean ovulation rate 1.4) were ovariectomized at oestrus during the breeding season. Each right ovary and 3 left ovaries were sectioned at 7 micron and examined microscopically. The number of small follicles, i.e. with 2 or less layers of granulosa cells, was estimated by a tested sampling procedure whilst all larger foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
1
1

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 9 publications
7
62
1
1
Order By: Relevance
“…The low percentage of degenerated follicles observed in this study coincides with other studies [16,51]. The histological analysis of preantral follicles, in situ and isolated, showed that the degeneration is characterized by oocyte alterations while pycnotic bodies were not observed in granulosa cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The low percentage of degenerated follicles observed in this study coincides with other studies [16,51]. The histological analysis of preantral follicles, in situ and isolated, showed that the degeneration is characterized by oocyte alterations while pycnotic bodies were not observed in granulosa cells.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies, however, reported lower numbers of preantral follicles in goat [4] and sheep [20] ovaries. It is well-known that besides the species differences, preantral follicle populations may be affected by factors such as breed [16], age [18,21], hormone levels and reproductive stage [22], and nutrition [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, continuous follicular growth occurs in the pony mare in average physical condition in the middle of the breeding season, and one hormonally priveleged period is evident towards the end of luteal phase, as in cows (Marion and Gier, 1971 ;Mariana and Nguyen Huy, 1973), ewes (Turnbull, Braden and Mattner, 1977 ;Cahill et al, 1979) and women (Gougeon, 1979). A similar conclusion was reached by Wesson and Ginther (1981) …”
mentioning
confidence: 73%
“…Moreover, according to Ingram (1962) the atresia is a degenerative process of unknown duration. Cahill et al (1979) and Jorio et al (1991) have described that while the pycnosis of granulosa cells occurs in antral follicles, it is almost absent in preantral follicles.…”
Section: Discussionmentioning
confidence: 99%